2018
DOI: 10.1080/21678421.2018.1473443
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioral longitudinal assessment in ALS: the Italian Edinburgh Cognitive and Behavioral ALS screen (ECAS)

Abstract: The significant improvement of some ECAS scores over time supports the presence of possible practice effects, particularly in the memory domain, highlighting the need to accommodate for these in longitudinal assessments, through healthy controls groups or alternate versions. This work represents the first Italian ECAS follow-up study and confirms ECAS feasibility in patients with increasing physical disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 59 publications
0
25
1
Order By: Relevance
“…Indeed, nearly two-thirds of cases had some evidence of cognitive impairment in more advanced stages. In contrast to previous publications, [2][3][4][5][6][7] our data point to a correlation between the severity of motor impairment and the severity of cognitive deficits, and suggest that cognitive function may not remain stable in patients with ALS. Importantly, our data indicate that the presence of bulbar signs is strongly associated with more severe cognitive impairment at all stages of disease.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Indeed, nearly two-thirds of cases had some evidence of cognitive impairment in more advanced stages. In contrast to previous publications, [2][3][4][5][6][7] our data point to a correlation between the severity of motor impairment and the severity of cognitive deficits, and suggest that cognitive function may not remain stable in patients with ALS. Importantly, our data indicate that the presence of bulbar signs is strongly associated with more severe cognitive impairment at all stages of disease.…”
Section: Discussioncontrasting
confidence: 99%
“…Amyotrophic lateral sclerosis (ALS) can no longer be considered a disease limited to the motor system but rather a multisystem disorder that involves cognitive domains in at least half of the cases. 1 Longitudinal studies point to a relative stability of cognitive function in patients who are not impaired at first examination, and a progression of the impairment in patients already compromised, [2][3][4][5][6][7] although such studies are complicated by the progressive loss of speech and motor function in the hands that hinders the accuracy of neuropsychological testing and causes a high patient attrition rate, further complicating our ability to evaluate the pattern of cognitive impairment in patients with ALS over time. 2,3 A recent study performed on a cross-sectional clinical-based cohort of patients evaluated using the Edinburgh Cognitive and Behavioural ALS Screen (ECAS) has shown that cognitive and behavioural deficits are more frequent and severe with advanced disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…High scores indicate a more severe involvement 37 . The ECAS feasibility in ALS has been confirmed administering longitudinally this test in comparison with standard neuropsychological tests 38 .…”
Section: Ecasmentioning
confidence: 87%